IFCI Limited (B) - Singla, Chitra, (SAGE Knowledge. Cases., 2017)
IFCI Limited-a financial institution in India was struggling with issues of negative Capital Adequacy Ratio and high non-performing assets till 2007. The company had not done any business for a decade untill 2007. July, 2007 was the time when Atul Rai joined the company as the CEO. This case revolves around the various strategic initiatives taken by Rai and his team to help the firm turnaround. The main focus of the case is on the implementation of some of the key strategic decisions.